SMARCB1/INI1 loss in skull base conventional chordomas: a clinicopathological and molecular analysis - Righi, Alberto; Cocchi, Stefania; Maioli, Margherita; Zoli, Matteo; Guaraldi, Federica; Carretta, Elisa; Magagnoli, Giovanna; Pasquini, Ernesto; Melotti, Sofia; Vornetti, Gianfranco; Tonon, Caterina; Mazzatenta, Diego; et al. (Frontiers in Oncology, 2023)
Introduction: The loss of SMARCB1/INI1 protein has been recently described in poorly differentiated chordoma, an aggressive and rare disease variant typically arising from the skull base.Methods: Retrospective study aimed at 1) examining the differential immunohistochemical expression of SMARCB1/INI1 in conventional skull base chordomas, including the chondroid subtype; 2) evaluating SMARCB1 gene deletions/copy number gain; and 3) analyzing the association of SMARCB1/INI1 expression with clinicopathological parameters and patient survival.Results: 65 patients (35 men and 30 women) affected by conventional skull base chordoma, 15 with chondroid subtype, followed for >48 months after surgery were collected. Median age at surgery was 50 years old (range 9-79). Mean tumor size was 3.6 cm (range 2-9.5). At immunohistochemical evaluation, a partial loss of SMARCB1/INI1 (>10% of neoplastic examined cells) was observed in 21 (32.3%) cases; the remaining 43 showed a strong nuclear expression. Fluorescence in situ hybridization (FISH) analysis was performed in 15/21 (71.4%) cases of the chordomas with partial SMARCB1/INI1 loss of expression. Heterozygous deletion of SMARCB1 was identified in 9/15 (60%) cases and was associated to copy number gain in one case; no deletion was found in the other 6 (40%) cases, 3 of which presenting with a copy number gain. No correlations were found between partial loss of SMARCB1/INI1 and the clinicopathological parameters evaluated (i.e., age, tumor size, gender, tumor size and histotype). Overall 5-year survival and 5-year disease-free rates were 82% and 59%, respectively. According to log-rank test analysis the various clinico-pathological parameters and SMARCB1/INI1 expression did not impact on overall and disease free-survival.Discussion: Partial loss of SMARCB1/INI1, secondary to heterozygous deletion and/or copy number gain of SMARCB1, is not peculiar of aggressive forms, but can be identified by immunohistochemistry in a significant portion of conventional skull base chordomas, including the chondroid subtype. The variable protein expression does not appear to correlate with clinicopathological parameters, nor survival outcomes, but still it could have therapeutic implications.